Photovoltaic technology in Southern Arava of Israel: an analysis of public acceptance. Issue 1 (2nd January 2021) - DiPersio, Thomas; Liedtke, Nicoli; Rosenthal, Aaron; Wallace, Alexandra; Morris, Avigail; Bar-On, Isa; Halasah, Suleiman; Abu Hamed, Tareq
ABSTRACT : Israel's Southern Arava region has experienced a boom in solar infrastructure development since 2011. Public acceptance of renewable energy installations is key to their successful implementation. The objective of this paper is to understand the level of acceptance of solar installations among Southern Arava communities and identify the factors that contributed to the widespread implementation of solar infrastructure in the region. Surveys and semi-structured interviews were distributed to five local kibbutz communities and local solar developers to gauge their attitudes about renewable technology in general and their acceptance of solar installations in their community. The results point to strong acceptance of solar technology in this region. Several factors contributed to this high level of support including kibbutz co-ownership of solar assets, transparent communication between stakeholders, and the kibbutz decision-making structure.